Lipid Signaling in Plants - Munnik, Teun (Plant Cell Monographs, 2010)
This book highlights the current status of plant lipid signaling. Written by leading researchers in the field, the chapters include detailed information on the measurement, regulation and function of phospholipases, lipid kinases, lipid phosphatases, inositolpolyphosphates, polyphosphoinositides, phosphatidic acid and additional lipid signals, e.g. oxylipins, NAPE and sphingolipids. Together, it represents a timely and comprehensive update of the rapidly expanding field of lipid signaling in plant stress and development.